2012
DOI: 10.1002/mawe.201100893
|View full text |Cite
|
Sign up to set email alerts
|

Influence of manufacturing parameters on gear distortion

Abstract: Realising the system-oriented approach of "Distortion Engineering", the influence of multiple parameters on the distortion of cylindrical gears was investigated by design of experiments. Aim of this research work was to investigate the effect of production parameters before the final heat treatment. The established experimental design focuses on the analysis of two main parts of gear distortion. One part is the distortion of the teeth themselves; the other part is a displacement of the teeth due to the distort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Manufacturing steps are performed in industrial conditions in a Renault (French car manufacturer) plant. It has been observed that teeth distortion is a consequence of size and shape changes of the base-body [1]. As a consequence, by improving the understanding of shaft distortion and decreasing it, teeth distortion should be limited.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Manufacturing steps are performed in industrial conditions in a Renault (French car manufacturer) plant. It has been observed that teeth distortion is a consequence of size and shape changes of the base-body [1]. As a consequence, by improving the understanding of shaft distortion and decreasing it, teeth distortion should be limited.…”
Section: Objectivementioning
confidence: 99%
“…Nevertheless, heat treatment has side effects such as geometrical variations on global and local scales [1]. Industrially, it means that these defects sometimes lead to increase scrap rates.…”
Section: Introductionmentioning
confidence: 99%
“…Steinbacher and Kohlhoff present corresponding results and their interpretation, obtained for different experimental designs and carried out within the SFB 570 [12,13].…”
Section: Evaluation Examplementioning
confidence: 90%
“…A detailed description of each of the mechanical processing steps can be comprehended in the work of Kohlhoff [2].…”
Section: Gearsmentioning
confidence: 99%
“…For the process chain of cylindrical gear wheels the influences of the hardenability of steel melts, the forging and the different machining processes are attended in the investigations of Kohlhoff [2]. This paper deals with the heat treatment related distortion of gear wheels.…”
Section: Introductionmentioning
confidence: 98%